Habitat distribution and diversity of forest plant as feed resources of mouse deer (Tragulus javanicus) and barking deer (Muntiacus muntjak) in Nature Preserve of west and east Nusakambangan - WARTIKA ROSA FARIDA; LILY ENDANG SETYORINI; GOZALI SUMAATMADJA (Biodiversitas Journal of Biological Diversity, 2003)
The objectives of the research were to study on habitat distribution and the diversity of forest plants as feed resources of mouse deer (Tragulus javanicus) and barking deer (Muntiacus muntjak) was conducted in Nature Preserve ofNusakambangan. Preferred Habitat of mouse deer is the dense of bushes with many fallen dry leaves which seemingly theyuse for their mattress cover as well as the places with bush dense of zalacca palm and generally not far from the river.While the barking deer prefers the dense of bushes on the edges of forest with coarse grass grow there. Forest plants asfeed resources for mouse deer and barking deer found in this research consist of 34 species grouped in 21 families.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words : habitat, feed plant, Tragulus javanicus, Muntiacus muntjak.